Pelatihan Branding Dan Digital Marketing Di Optik Citra Padang - Rina Novalinda (CV. ITTC INDONESIA, 2023)
Currently there are many social media platforms that have been created over time due to technological developments. Currently, social media platforms such as Facebook, Twitter, Path, Instagram, and YouTube are becoming popular, especially during the pandemic, and are used as one of the tools that are widely used by business people in developing their business by expanding business networks, introducing business programs and products. , social media is needed for various needs both for exchanging information, outreach to as a medium for promotion. Community service is a form of higher education concern in providing knowledge in improving the quality of HR (Human Resources) to Community service partners in this activity are Optik Citra Padang with the participants involved coming from the staff. The problem partners are currently experiencing is that they still do not understand the use of technology and social media in branding strategies which are currently popular and in addition to providing knowledge to increase skills for Optik Citra Padang employees. Through this community service activity, we will provide a solution to this problem by providing HR Quality Improvement Training in Branding Strategies Through Digital Marketing at Optik Citra Padang. In terms of technical implementation, this community service activity is carried out in Hybrid (Online and Offline), with this activity it is hoped that knowledge about the use of digital media will increase for the training participants.